Hormonal contraception and risk of cancer - Cibula, D; Gompel, A; Mueck, A O; La Vecchia, C; Hannaford, P C; Skouby, S O; Zikan, M; Dusek, L (Human reproduction update, 2010)
BACKGROUND: Fear from increased cancer risk is one of the most significant reasons for low acceptance of reliable contraceptive methods and low compliance. METHODS: In this review, we included all cohort and case-control studies published in English up to December 2008. They were identified through a search of the literature using Pubmed and EMBASE. RESULTS: Data about breast cancer risk indicate a slightly increased risk among current users of oral contraceptives (OC), an effect which disappears 5-10 years after stopping. Combined OC have a significant protective effect on the risk of ovarian cancer, and the protection increases with duration of use (relative risk decreased by 20% for each 5 years of use). The significant risk reduction has been confirmed for BRCA 1 and 2 mutation carriers. The risk of endometrial cancer is reduced by about 50% in ever users, a benefit which is greater with increasing duration of use. An association has been found between increased risk of cervical cancer and long-term OC use. Current OC use has been associated with an excess risk of benign liver tumours and a modest increased risk of liver cancer. None of large prospective cohort studies with prolonged follow-up has observed an increased overall risk of cancer incidence or mortality among ever users of OC, indeed several have suggested important long-term benefits. Specifically, protective effect of OC can be used as chemoprevention in young women who are BRCA mutation carriers. CONCLUSIONS: Women wishing to use combined OC can be reassured that their decision is unlikely to place them at higher risk of developing cancer.
Keywords: časové faktory; nádory prsu; Ovarian Neoplasms; Neoplasms; nádory endometria; Lung Neoplasms; nádory jater; lidé; Humans; Uterine Cervical Neoplasms; nádory děložního čípku; Genes, BRCA1; kohortové studie; Colorectal Neoplasms; geny BRCA1; Genes, BRCA2; Time Factors; nádory plic; Risk Assessment; nádory; kontraceptiva orální hormonální; kolorektální nádory; Meta-Analysis as Topic; metaanalýza jako téma; hodnocení rizik; Case-Control Studies; Liver Neoplasms; Cohort Studies; ženské pohlaví; Contraceptives, Oral, Hormonal; Endometrial Neoplasms; geny BRCA2; Female; studie případů a kontrol; nádory vaječníků; Breast Neoplasms